159 SUCCESSFUL USE OF INFLIXIMAB IN THE TREATMENT OF REITER'S SYNDROME: A CASE REPORT. (1st January 2006) - Gill, H.; Majithia, V.
Abstract : Introduction: Reiter's syndrome is one of the reactive forms of spondyloarthropathies. The clinical syndrome consists of a triad of asymmetric oligoathritis, urethritis, and conjunctivitis. It is also associated with characteristic mucocutaneous lesions. Various therapies used in the management are NSAIDs, antibiotics, and DMARDs such as SSZ or methotrexate. There is only 1 case report of successful treatment of Reiter's syndrome with TNF-a blockers in an HIV+ patient. We report a case of Reiter's syndrome treated successfully with infliximab. Case Report: A 28-year-old white male presented with painful swelling of right elbow and ankle joints, urethritis, and lesions involving skin of soles of feet and penis. No other joint was involved. He also complained of fatigue, fever, and mild sore throat, but, otherwise, his review of systems, past, social and family history was negative. He was sexually active with one partner and denied any history of sexually transmitted disease. Pertinent positives on physical examination were synovitis of right elbow and ankle joints. He had extensive skin lesion on soles and penis consistent with keratoderma blennorrhagica and circinate balanitis. Laboratory workup was positive for a high WBC count of 13, 700 cells/mm 3, ESR of 82, and CRP of 11.1. Detailed workup of STDs, HIV, and systemic etiology was negative. Despite aggressive treatment with antibiotics, NSAIDS, prednisone, and methotrexate, he had persistent synovitis and worsening of skin lesions. Due to severity and resistance of disease to the conventional treatment modalities, infliximab therapy was instituted, which resulted in complete resolution of arthritis and skin lesions within 6 weeks of infliximab therapy. Discussion and Conclusion: There is a lot of evidence supporting the use of TNF-a blockers in other seronegative spondyloarthropathies, such as psoriatic arthritis and AS, but there is only 1 previous case report of its use in Reiter's syndrome. Although this use is intuitive, there is a theoretical potential as well as animal data suggesting its possible benefit. The successful use of infliximab in this patient with Reiter's syndrome as well as rapid improvement in severe skin lesions and arthritis suggests a significant role of TNF-a in the pathogenesis of this disease. This is an encouraging preliminary result, and we suggest that the use of TNF-a blockers in Reiter's syndrome should be further investigated.